Paraneoplastic LGI1 Encephalitis Associated with Lung Adenocarcinoma: A Case Report - Francesco Rossato; Andrea Porsio; Diego Cecchin; Matteo Atzori; Anna Maria Basile; Marco Zoccarato (NeuroSci)
Limbic encephalitis (LE) associated with anti-LGI1 antibodies is an autoimmune disorder characterized by memory decline, behavioral changes, and temporal lobe epilepsy. Faciobrachial dystonic seizures (FBDS) are a hallmark symptom, often preceding cognitive and psychiatric issues. This report presents an 80-year-old male with LGI1 encephalitis, initially manifesting as FBDS. A lung adenocarcinoma was diagnosed two months after the onset of neurological symptoms. Clinical and paraclinical data, including MRI and [18]FDG PET imaging, are described. The patient responded to immunotherapy, including steroids and plasma exchange, along with tumor resection. Following treatment, neurological symptoms resolved, except for mild anxiety and apathy. Further research is needed to determine whether LGI1 encephalitis may occasionally have a paraneoplastic origin, potentially influencing screening and management strategies.